2017
DOI: 10.1021/acs.inorgchem.7b01483
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Water-Splitting with Organomanganese Complexes

Abstract: Certain organometallic chromophores with water-derived ligands, such as the known [Mn(CO)(μ-OH)] (1) tetramer, drew our attention as possible platforms to study water-splitting reactions. Herein, we investigate the UV irradiation of various tricarbonyl organomanganese complexes, including 1, and demonstrate that dihydrogen, CO, and hydrogen peroxide form as products in a photochemical water-splitting decomposition reaction. The organic and manganese-containing side products are also characterized. Labeling stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 57 publications
4
16
0
Order By: Relevance
“…Therefore, today's research is increasingly oriented on utilizing renewable harvesting technologies (wind turbines or photovoltaics) to drive the electrochemical/catalytic water-splitting reaction. Photochemical [35,36]/photocatalytic [37,38] water splitting is a promising option for hydrogen production, which is oriented on the reduction of CO 2 -emission and applications of renewable resources such as water and sunlight. The most important criteria for solar-driven water splitting reactions is the electronic bandgap alignment of the photosensitive material with the redox potential of water [37].…”
Section: Spinel Mixed Oxides For Chemical-loop Reformingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, today's research is increasingly oriented on utilizing renewable harvesting technologies (wind turbines or photovoltaics) to drive the electrochemical/catalytic water-splitting reaction. Photochemical [35,36]/photocatalytic [37,38] water splitting is a promising option for hydrogen production, which is oriented on the reduction of CO 2 -emission and applications of renewable resources such as water and sunlight. The most important criteria for solar-driven water splitting reactions is the electronic bandgap alignment of the photosensitive material with the redox potential of water [37].…”
Section: Spinel Mixed Oxides For Chemical-loop Reformingmentioning
confidence: 99%
“…The most important criteria for solar-driven water splitting reactions is the electronic bandgap alignment of the photosensitive material with the redox potential of water [37]. In general, the presence of transition metal cations with a d 0 electronic configuration (Ta 5+ , Ti 4+ , Zr 4+ , Nb 5+ , Ta 5+ , W 6+ , and Mo 6+ ), or metal cations with a d 10 electronic configuration (In 3+ , Sn 4+ , Ga 3+ , and Ge 4+ ) is considered to be important for the efficient photocatalytic materials, the empty d or sp orbitals of which form the bottom of the respective conduction bands [36]. Over the last decades, significant progress in this field To protect the rights of the author(s) and publisher we inform you that this PDF is an uncorrected proof for internal business use only by the author(s), editor(s), reviewer(s), Elsevier and typesetter SPi.…”
Section: Spinel Mixed Oxides For Chemical-loop Reformingmentioning
confidence: 99%
“…[24] Moreover, studies conducted in aqueous solution have increased the attention to the contribution of hydrogen bonds in the control of coordinated water acidity and its consequences, such as hydrogen evolution from photolysis of MnÀ OH 2 complexes. [25][26][27] Recent studies have explored this in detail, as the one using a tetramer cluster composed of four Mn metals with hydroxyl bridge groups between them, [Mn(CO) 3 (μ 3 -OH)] 4 . Under illumination, one CO is lost and the Mn(I) center oxidizes to Mn(II), which is stabilized when the proton from the À OH is transferred through hydrogen bonds to 2,2,6,6-tetramethylpiperidine (TEMPO), forming the spin adduct TEMPOÀ H. [28] The previous studies and this work have the following in common: use of light to trigger the initial reaction, the liberation of CO, and increase in manganese oxidation states to overcome the next steps during photolysis, such as electron transfer and improved electrochemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…The manganese and calcium metal ions are bridged by five oxygen atoms and four water molecules that are bound to this cluster, where two of them are proposed to be substrates in reaction . , Even though the reaction mechanism at the OEC is not yet completely elucidated, it is one of the most studied catalytic systems. , A variety of small molecule structural and functional mimics of OEC have also been explored and developed ,, to find a better photocatalyst for the water oxidation reaction. To this end, manganese oxide complexes consisting of a single metal ion or two metal ions bridged by μ-oxo groups have been considered both experimentally and theoretically. ,,,,,,, Density functional theory (DFT) calculations performed by Blomberg et al using the B3LYP/6-311+G­(d,p) level of theory suggested that hydrogen abstraction from a water molecule is lowered in energy upon binding to a monomeric or dimeric manganese complex. Moreover, they proposed possible functions of a coordinated chloride and a nearby Ca 2+ ion during the oxygen-evolving process.…”
Section: Introductionmentioning
confidence: 99%